Single-longitudinal-mode operation in tunable novel zirconia-yttria-alumina-erbium-doped fiber laser - Ahmad, Harith; Thambiratnam, K.; Paul, M.C.; Harun, Sulaiman Wadi (IOP Publishing, 2014)
A tunable, single-longitudinal-mode (SLM) fiber laser based on a short length, highly doped zirconia–erbium doped fiber (Zr-EDF) is proposed and demonstrated. The Zr-EDF is a novel fiber with an erbium ion concentration of 4320 ppm wt − 1 and an absorption rate of approximately 22.0 dB m − 1 at 978 nm, while at the same time being highly compatible with conventional silica-based optical fibers. The Zr-EDF is used as the gain medium in the laser cavity, while a tunable C-band fiber Bragg grating is used to adjust the operating wavelength of the system, providing an operating wavelength range of between 1533.8 nm to 1545.0 nm. Two short erbium-doped fibers, with active ion concentrations of 900 ppm wt − 1, serve as saturable absorbers, and allow for an SLM output with a narrow laser linewidth of only 0.2 MHz. The proposed system has multiple applications as a tunable SLM laser for communications and sensing purposes.